Applying Machine Learning to RNA Secondary Structure Prediction Problem - Doan, Duy Binh (Vietnam-Korea University of Information and Communication Technology, 2023)
Proceeding of The 12th Conference on Information Technology and It's Applications (CITA 2023); pp: 33-44.